EVALUASI LAYANAN PENGADUAN KOTA SEMARANG : STUDI PENANGANAN KASUS KERUSAKAN JALAN PERIODE 2021-2022 - Sunaringtyas, Karima Azzahra; -, supratiwi -; Erowati, dewi - (Journal of Politic and Government Studies, 2024)
The background to this research is the importance of evaluating the complaint management process using a case study of one of the crucial reports received through the LAPOR HENDI service during the 2021-2022 period, namely a case of road damage. The total number of road damage reports received in 2021 reached 212 reports, and in 2022 it reached 266 reports. This research uses a qualitative method with a case study approach, and uses primary and secondary data. The research location is in Semarang City, Central Java. Data collection methods include interview techniques, observation, documentation and literature study. Based on the research results obtained, the Semarang City complaint service for the 2021-2022 period has succeeded in managing complaints in handling road damage reports. This success is based on fulfilling four evaluation criteria by William N. Dunn, namely effectiveness, equity, responsiveness, and appropriateness. The recommendations given are related to the mechanism for closing reports, developing independent networks, and socializing road sections to the community.